1990
DOI: 10.1080/09593339009384931
|View full text |Cite
|
Sign up to set email alerts
|

Photosonochemical decomposition of aqueous 1,1,1 ‐ trichloroethane

Abstract: This study describes development of 1,1,1-trichloroethane removal from aqueous solutions. The decomposition of aqueous 1,1,1-trichloroethane is more extensive with combined photolysis and sonolysis process than each separately. The extent of decomposition is measured by gas Chromatograph for removal of CCl 3 CH 3 , by a turbidometric procedure for production of chloride ions, and Fourier transform infrared spectroscopy for solid product. The concept is to degrade CCl 3 CH 3 in water flow systems to chloride io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…This optimum value of the volume of the effluent also depends on the operating conditions of the reactor mainly the magnitude of power supplied (which will decide the rate of generation of free radicals) and the type of the effluent in question (the rate constant for the reaction between the pollutant and free radicals is equally important). Toy et al (1990) obtained better results for the combination techniques at volumes as low as 3 to 4 mL, whereas Chen and Smirniotis (2002) reported that the synergistic effects of using the combination technique are more pronounced at lower volumes of treatment (relative enhancement was 82% at 50 mL, whereas it was 29% for 300 mL). It appears that too much cavitation at lower volumes can be detrimental (for individual operation or the combination technique), possibly attributable to the fact that the density of cavitation bubbles is higher in small volumes, which are continuously in the zone of influence of the transducers and result in relatively larger bubble sizes (ascribed to coalescence) decreasing the collapse intensity (Gogate and Pandit, 2000) and also possibly affecting the UV transmission rates.…”
Section: Sonophotocatalytic Oxidationmentioning
confidence: 99%
“…This optimum value of the volume of the effluent also depends on the operating conditions of the reactor mainly the magnitude of power supplied (which will decide the rate of generation of free radicals) and the type of the effluent in question (the rate constant for the reaction between the pollutant and free radicals is equally important). Toy et al (1990) obtained better results for the combination techniques at volumes as low as 3 to 4 mL, whereas Chen and Smirniotis (2002) reported that the synergistic effects of using the combination technique are more pronounced at lower volumes of treatment (relative enhancement was 82% at 50 mL, whereas it was 29% for 300 mL). It appears that too much cavitation at lower volumes can be detrimental (for individual operation or the combination technique), possibly attributable to the fact that the density of cavitation bubbles is higher in small volumes, which are continuously in the zone of influence of the transducers and result in relatively larger bubble sizes (ascribed to coalescence) decreasing the collapse intensity (Gogate and Pandit, 2000) and also possibly affecting the UV transmission rates.…”
Section: Sonophotocatalytic Oxidationmentioning
confidence: 99%
“…Without a catalyst, the additive or synergistic effects of UV and US were reported by Hamdaoui and Naffrechoux (2008), Naffrechoux et al (2003), and Rong et al (2003). Wu et al (2001) and Toy et al (1990) found an enhanced degradation efficiency using UV and US concurrently without a catalyst, although they did not indicate the reactions were either additive or synergistic.…”
Section: Tca Tce and Pce Degradation At T D =60 Minmentioning
confidence: 90%
“…Rong et al (2003) observed the synergistic effect of UV (260 nm; 0.4 to 2.1 W) and US (500 kHz; 16-24 W) on the decomposition of p-chlorophenol in a batch reactor. Toy et al (1990) observed that the extent of TCA decomposition with UVUS was greater than UV (200-watt Hg) and US (20 kHz) separately in a batch reactor study without a catalyst.…”
Section: Tca Tce and Pce Degradation At T D =60 Minmentioning
confidence: 90%
See 1 more Smart Citation
“…The rate of decon^osition of aqueous 1,1,1-trichloroethane was higher in the presence of both photolysis and sonolysis when con^pared to the use of either technique alone (Toy et al, 1990). When both techniques were used simultaneously, the authors referred to the process as '^photosonochemical".…”
Section: Photolysismentioning
confidence: 99%